2014
DOI: 10.1111/bjet.12159
|View full text |Cite
|
Sign up to set email alerts
|

Technological utopia, dystopia and ambivalence: Teaching with social media at aSouthAfrican university

Abstract: The discourse of social media adoption in higher education has often been funnelled through utopian and dystopian perspectives, which are polarised but determinist theorisations of human engagement with educational technologies. Consequently, these determinist approaches have obscured a broadened grasp of the situated, socially constructed nature of human interaction with educational technologies and failed to explain ambivalent positions of technology adoption. To contest the innate determinism embodied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Internet addiction has been described as a twenty-first century epidemic (Christakis, 2010). There is growing evidence that because of their hyperlinked architecture social media can prove more distracting than focusing (Aagaard, 2014;Anderson et al, 2014;Rambe and Nel, 2014). Along with this, other research has provided clear evidence that overuse or maladaptive use of ICT can have negative effects on the well-being and psychological functioning of children, adolescents, and young adults (Brooks, 2015;Fox and Moreland, 2015;Rosen et al, 2013;Sampasa-Kanyinga and Lewis, 2015).However, social media is simply providing a quicker peeling of the onion as in majority of the cases the issues were anyway there and most people anyway love to talk about themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Internet addiction has been described as a twenty-first century epidemic (Christakis, 2010). There is growing evidence that because of their hyperlinked architecture social media can prove more distracting than focusing (Aagaard, 2014;Anderson et al, 2014;Rambe and Nel, 2014). Along with this, other research has provided clear evidence that overuse or maladaptive use of ICT can have negative effects on the well-being and psychological functioning of children, adolescents, and young adults (Brooks, 2015;Fox and Moreland, 2015;Rosen et al, 2013;Sampasa-Kanyinga and Lewis, 2015).However, social media is simply providing a quicker peeling of the onion as in majority of the cases the issues were anyway there and most people anyway love to talk about themselves.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have also found that this does not have to impact on their ability to access the technology necessary for learning. On the contrary, as others have shown, students are resourceful in finding complex and nuanced ways of engaging with technologies for teaching and learning within broader structural conditions (Czerniewicz, Williams & Brown, ; Rambe & Nel, ). The results however also show that not all students can rely on their own mobile technology to access podcasts and that the institutional provision of computer labs might still be an important aspect in terms of providing an equitable access to technology for all students.…”
Section: Discussionmentioning
confidence: 97%
“…Collaborative, constructivist modes of teaching may be enhanced by social media. However, the research is scattered and mixed, exposing possible dystopian and utopian views (Rambe and Nel 2015 ;Manca and Ranieri 2016 ). When we consider the educator ' s perceptions and facility with social media, a utopian view is not certain; rather, many dystopian views are possible depending on how and why social media is implemented in instruction.…”
Section: Critique Of Social Mediamentioning
confidence: 99%